Development of the Drosophila mushroom bodies: elaboration, remodeling and spatial organization of dendrites in the calyx. - Zhu, S.; Chiang, A.S.; Lee, T. (Development, 2003)
One Drosophila mushroom body (MB) is derived from four indistinguishable cell lineages, development of which involves sequential generation of multiple distinct types of neurons. Differential labeling of distinct MB clones reveals that MB dendrites of different clonal origins are well mixed at the larval stage but become restricted to distinct spaces in adults. Interestingly, a small dendritic domain in the adult MB calyx remains as a fourfold structure that, similar to the entire larval calyx, receives dendritic inputs from all four MB clones. Mosaic analysis of single neurons demonstrates that MB neurons, which are born around pupal formation, acquire unique dendritic branching patterns and consistently project their primary dendrites into the fourfold dendritic domain. Distinct dendrite distribution patterns are also observed for other subtypes of MB neurons. In addition, pruning of larval dendrites during metamorphosis allows for establishment of adult-specific dendrite elaboration/distribution patterns. Taken together, subregional differences exist in the adult Drosophila MB calyx, where processing and integration of distinct types of sensory information begin.